The The pandeirista and his multiple activities in the field of musical work (Orfeu, 2024)
This article intends to carry out a bibliographical review about the performance of some prominent Brazilian tambourine players and their situation as workers . We sought to obtain records available at different moments in the historiography of Brazilian music. To talk about the contemporary period, data was used about four tambourine players whose trajectories have been followed in ongoing doctoral research.
Keywords: pandeiro; labour; history